2012
DOI: 10.5603/cj.2012.0118
|View full text |Cite
|
Sign up to set email alerts
|

Emergency polytetrafluoroethylene-covered stent implantation to treat right coronary artery perforation during percutaneous coronary intervention

Abstract: (Cardiol J 2012; 19, 6: 639-642)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Its incidence was reported to be 0.2% -0.6% [1,2].The diagnosis and classification of coronary perforation have been shown in the previous studies [3,4]. In our country, this situation was reported only as case reports in the medical literature, but there was no prospective study about this issue [5]. The interventions performed for type B and C lesions defined in AHA/ACC, and athero ablation procedures that are increasingly practiced have increased the frequency of the occurrence of perforation [6,7].…”
Section: Introductionmentioning
confidence: 38%
“…Its incidence was reported to be 0.2% -0.6% [1,2].The diagnosis and classification of coronary perforation have been shown in the previous studies [3,4]. In our country, this situation was reported only as case reports in the medical literature, but there was no prospective study about this issue [5]. The interventions performed for type B and C lesions defined in AHA/ACC, and athero ablation procedures that are increasingly practiced have increased the frequency of the occurrence of perforation [6,7].…”
Section: Introductionmentioning
confidence: 38%
“…The process of study selection is shown in Figure 1. From a total of 319 studies in our search, only 29 reports were included in the analysis 6,8–35 . The description of the included studies is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Several devices have been introduced to repair coronary perforations occurring during PCI. Among them, the most popular devices are polytetrafluoroethylene-covered stents made of an inert and biocompatible polymer composed of carbon chains saturated with fluorine (7,9). However, emergency CABG is usually necessary in severe Ellis Type III perforations and cases with hemodynamic compromise even after successful covered stent implantation (1,10).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac tamponade, myocardial infarction and even death are potential complications (6). Therapeutic options include emergency coronary artery bypass grafting (CABG) surgery, covered stent implantation and embolisation if perforation occurs at distal segments of the coronary artery (7). Previously, Ellis et al (4) described a classification for coronary perforations.…”
Section: Introductionmentioning
confidence: 99%